PENERAPAN STRATEGI PEMBELAJARAN INDEX CARD MATCH UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VII.6 SMPN 12 PEKANBARU PADA MATERI KLASIFIKASI MAKHLUK HIDUP - Eva Murniati (STKIP Pesisir Selatan, 2019)
The selection of the right learning method greatly affects the high and low learning outcomes of students. At Pekanbaru SMPN 12, the learning strategies used by science teachers are still conventional. Learning has been teacher-centered and communication runs in one direction. The lecture method does not provide space for students to develop their knowledge. Passive learners and learning become boring. So the science learning outcomes of class VII.6 students are low. Therefore, it is necessary to conduct research on science learning by applying learning strategies that can involve students actively and can improve student learning outcomes. Index Card Match strategy is an active learning method for reviewing subject matter with a technique of finding index card pairs which are answers or questions while learning about a concept or topic in a pleasant atmosphere. One of them is by using Index Card Match learning strategies. The formulation of the problem in this research is